Analysis of the relationship between the application of negotiation style and conflict management strategies physical education's experts in Iran - Mojtaba Hassannejad; Ali Zarei; Farideh Ashrafganjouei (Turkish Journal of Kinesiology, 2017)
The conflict is a major behavioral complication of groups. The manager who knows the basic principles of conflict and negotiation will be ready to deal successfully with these inevitable situations. However, this study aimed to explain the role of negotiation in conflict management among physical education experts in Education and Training System of Iran. This study applied analytical- correlation study. The sample consisted of 217 physical education experts. The Robbins' Conflict Management Questionnaire and PEER's Negotiation Styles Questionnaire (1989) were used for collecting the data. The findings showed that there is a significant relationship between negotiation styles and conflict management. However, there was no relationship between negotiation styles and avoidance strategy.  The factual style and solution-oriented strategy were selected by participants. It was concluded that the negotiation styles and conflict management strategies should be used considering the situation.  It was recommended that the training courses would be hold to increase the skills of physical education managers and empower them.